A bioactive new protostane-type triterpenoid from Alisma plantago-aquatica subsp. orientale (Sam.) Sam. Issue 6 (19th March 2019) - Wang, Ya-Li; Zhao, Jian-Chao; Liang, Jia-Hao; Tian, Xiang-Ge; Huo, Xiao-Kui; Feng, Lei; Ning, Jing; Wang, Chao; Zhang, Bao-Jing; Chen, Gang; Li, Ning; Sun, Cheng-Peng
Abstract: A new protostane-type triterpenoid, 5 β, 29-dihydroxy alisol A (1 ) was isolated from Alisma plantago - aquatica subsp . orientale (Sam.) Sam. as well as 12-deoxyphorbol-13 α -pentadecanoate (2 ). We first report the presence of compound2 in the genus Alisma . Their structures were established on the basis of 1D and 2D NMR, and HRESIMS spectroscopic analyses. All the isolated compounds were assayed for their inhibitory effects against human carboxylesterase 2 (HCE-2). Compounds1 and2 displayed inhibitory activities against HCE-2 with IC50 values of 29.2 and 4.6 μM, respectively. The interaction mechanisms of HCE-2 with compounds1 and2 were investigated by molecular docking, respectively. Abstract :